The Effect of Drill Training Method on Badminton Backhand Hit Skills at PB Club. Sarma Pangkalpinang - Ramadhan, Sahrul; Putranto, Dedy; Oktarina, Oktarina (Journal of Physical Education Innovation, 2024)
Lack of proficiency in badminton backhand shots was the driving force behind this study. Through analysis during the initial observation, the researcher found that there were still training patterns that had yet to be considered so that they were more reproduced in games. There was no variety of exercises applied. Therefore, researchers researched to determine the effect of the drill training method on badminton backhand shot skills. This type of research is quantitative research using the "pre-experimental design" research method, namely One-Group et al. The population in this study were all PB—Sarma Pangkalpinang athletes, totaling 20 people. The sample in this study was all members of the population. The data analysis technique in this study uses normality tests and hypothesis testing. The count value of 18.728 is higher than the t table value of 1.729, which means that Ho is not true and Ha is true. This means that the study titled "The Effect of the Drill Training Method on Badminton Backhand Hit Skills at Club PB. Sarma Pangkalpinang" has a significant effect.